The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/su11226504
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk Silica Enhances Innate Immune in Zebrafish (Danio rerio) and Improves Resistance to Aeromonas hydrophila and Streptococcus iniae Infection

Abstract: Rice husk (RH) contains abundant silica such that RH silica (RHS) may be useful for possible industrial exploitation. Here, amorphous silica nanoparticles with multiple pore structures were acquired from RH by simple thermochemical processes. RHS antimicrobial activity and effects on zebrafish innate immunity against pathogen infections were evaluated. A toxicity assay showed that zebrafish exposed to an RHS dose lower than 200 μg/mL did not exhibit damage to zebrafish embryonic development or juvenile surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The detailed process of rice husk preparation is shown in previous studies [13]. Briefly, the production of rice husk silica (RHS) involves smoldering rice husk samples (PIN FU FA Corporation, Yunling, Taiwan) at a temperature of 300 • C for 2 h in a low-oxygen environment (oxygen concentration less than 5%), and then firing them at a temperature of 800 • C for 2 h in the atmosphere.…”
Section: Reagent Preparationmentioning
confidence: 99%
“…The detailed process of rice husk preparation is shown in previous studies [13]. Briefly, the production of rice husk silica (RHS) involves smoldering rice husk samples (PIN FU FA Corporation, Yunling, Taiwan) at a temperature of 300 • C for 2 h in a low-oxygen environment (oxygen concentration less than 5%), and then firing them at a temperature of 800 • C for 2 h in the atmosphere.…”
Section: Reagent Preparationmentioning
confidence: 99%
“…Or it can be explained by the decreased egg hatching rate, with the used metals (Pd‐Cu) limiting the physical movement of the embryos and interfering with the activities of the hatching enzymes necessary for the embryo to digest the chorion. [ 9,43–47 ] The previous studies with different metallic NPs had also stated that the hatchability of D. rerio embryos is negatively affected (nano‐palladium, [ 27 ] Ag NPs, [ 48 ] gold and silver NPs, [ 49 ] RP‐Ag/ACNPs, [ 47 ] gold NPs, RP‐Pd/AC NPs [ 9 ] ). As expected, a very small particle size will facilitate the passage of the particle through the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…[42] Our data on embryonic development are consistent with previous literature. [42,43] NP can act as a foreign body, restraining the normal activity of the organ or cell in which it accumulates. It can be thought that the larvae are not awaited to survive under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The RHSL and FDSL used in this study were formulated according to the silicon concentration, and the high dose contained about 100 ppm of silicon, which is within the safe range. Our previous study showed that zebrafish embryos and juveniles were not affected in terms of survival, hatching, or deformity rates when exposed to less than 200 µg/mL RHS and displayed a healthy physiological state [ 18 ]. Silicon dioxide is an atomic crystal that is insoluble in water and requires a strong alkali to dissolve.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed process of rice husk preparation can be found in previous studies [ 18 ]. In addition, the production process and the conditions of aqueous RHSL (rice-husk silica liquid) were performed according to our previous research [ 16 ].…”
Section: Methodsmentioning
confidence: 99%